(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the value of computed tomography in the treatment of nephroblastoma in children with neoadjuvant chemotherapy at Children’s Hospital 2. Methods: Cross sectional study. Results: From April 2013 to June 2016, there were 75 cases were diagnosed as nephroblastoma on computed tomography and treated with neoadjuvant chemotherapy. The rate of confirmed diagnosis of nephroblastoma on computed tomographic appearances consistent with pathological results was 85.3%. Pre- and post-chemotherapy computed tomography appearances are valuable in assessing the impact of chemotherapy on nephroblastoma: The rate of invasive perinephric fat tumors decreased from 85.9% to 43.8%. The rate of vascular invasive tumors decreased from 20.3% to 6.3%. The rate of regional lymph node metastasis decreased from 20.3% to 4.7%. The distant metastatic lesions all disappeared. The tumor volume reduced from 487.9 cm3 to 206.8 cm3. The percentage increased from 0% to 56.3% in stage I disease; decreased from 78.1% to 37.5% in stage II disease; decreased from 18.8% to 6.3% stage III disease; and decreased from 3.1% to 0% in stage IV disease. The overall response rate was 89.1%. Conclusions: Computed tomography plays an important role in the treatment of nephroblastoma according to neoadjuvant chemotherapy regimen, helping to assess changes in tumor characteristics, stage, volume, and chemotherapy response when performing nephrectomy after chemotherapy, creating favorable conditions for surgeons to orient safer surgery with fewer complications.